Literature Review : Analisis Fungsi Penawaran dalam Ekonomi Mikro - Rani Yunita Sari Sagala; Winona Keysadli; Verani Sinurat; Khairani Alawiyah Matondang (Trending: Jurnal Manajemen dan Ekonomi, 2025)
This journal discusses the concept of the supply function in microeconomics, which is a fundamental element in understanding the interaction between price and the quantity of goods offered by producers. This research aims to explain the meaning of the supply function, describe the supply curve, and analyze the factors that cause shifts in the supply curve. Using an analytical approach, this paper shows that the supply curve usually has a positive slope, reflecting that the higher the price of a good, the greater the quantity of the good supplied. In addition, shifts in the supply curve can be influenced by various factors such as changes in production costs, technology, government policies, and the number of producers in the market. It is hoped that the results of this analysis can provide students and researchers with a better understanding in analyzing market dynamics and making more effective decisions. Suggestions for producers and the government were also provided to increase production efficiency and market stability.